2009
DOI: 10.1152/jn.90815.2008
|View full text |Cite
|
Sign up to set email alerts
|

Differential Influence of Attention on Gaze and Head Movements

Abstract: Khan AZ, Blohm G, McPeek RM, Lefèvre P. Differential influence of attention on gaze and head movements. J Neurophysiol 101: 198 -206, 2009. First published November 5, 2008 doi:10.1152/jn.90815.2008. A salient peripheral cue can capture attention, influencing subsequent responses to a target. Attentional cueing effects have been studied for head-restrained saccades; however, under natural conditions, the head contributes to gaze shifts. We asked whether attention influences head movements in combined eye-head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…Functionally, a unitary displacement of the gaze from one target location to another is typically effected by a minimum of two partly independent but linked motor systems, those of eyes and head. The most caudally located premotor site for unitary specification of gaze displacements is the superior colliculus in the roof—tectum—of the midbrain [(Munoz et al, 1991; Freedman et al, 1996; Freedman and Sparks, 1997; Scudder et al, 2002); reviewed in Sparks (2004); see also (Khan et al, 2009)]. Downstream from the superior colliculus the circuitry for control of eyes and head again diverge (Masino, 1992; Scudder et al, 2002; Sparks, 2004; Horn, 2006).…”
Section: Picking a Path Through The Wildernessmentioning
confidence: 99%
“…Functionally, a unitary displacement of the gaze from one target location to another is typically effected by a minimum of two partly independent but linked motor systems, those of eyes and head. The most caudally located premotor site for unitary specification of gaze displacements is the superior colliculus in the roof—tectum—of the midbrain [(Munoz et al, 1991; Freedman et al, 1996; Freedman and Sparks, 1997; Scudder et al, 2002); reviewed in Sparks (2004); see also (Khan et al, 2009)]. Downstream from the superior colliculus the circuitry for control of eyes and head again diverge (Masino, 1992; Scudder et al, 2002; Sparks, 2004; Horn, 2006).…”
Section: Picking a Path Through The Wildernessmentioning
confidence: 99%
“…Contemporary research continues to explore the nature and degree of functional and neural overlap between eye movements and attention, as well as the mechanisms which enable the two functions to be dissociated during covert attention (e.g. Juan et al 2004;Cohen et al 2009;Khan et al 2009;Lawrence and Snyder 2009;Bisley and Goldberg 2010;see also Deubel (in chapter 30), this volume, Theeuwes (in chapter 8), this volume; Gottlieb and Balan 2010;Wardak et al 2011;Belopolsky and Theeuwes 2012;Gregoriou et al 2012). Although oculomotor circuits may play a primary role in the network for spatial attention, studies have suggested that other sensorimotor circuits, specialized for different forms of spatially guided action (e.g.…”
Section: Relationship Between Visuospatial Attention and Oculomotor Cmentioning
confidence: 99%
“…Note that many regions known to be involved in saccadic eye movements such as the FEF or the SC are also involved in combined eye-head movements. Several studies shown that a single gaze controller is responsible for programming both the eye and the head (e.g., Khan, Blohm, McPeek, & Lefevre, 2009). In this regard, proponents of OMRH/premotor theory might argue that the ability to prepare for a combined eyehead movement could have still mediate attention shifts (e.g., Cicchini, Valsecchi, & de'Sperati, 2008).…”
Section: Discussionmentioning
confidence: 99%